2020
DOI: 10.3382/ps/pez560
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and incidence of broiler chicken wooden breast meat under commercial conditions in China

Abstract: Wooden breast (WB) has emerged as a dramatically increasing myopathy in the poultry industry over the past few years. The objective of this study was to investigate the incidence of WB in a Chinese commercial broiler processing plant, and the consequences on quality attributes, textural properties, and sensory traits. A total of 1,135 breast fillets were collected at the deboning line and assigned to normal, mild, moderate, and severe WB categories by tactile evaluation. The proportion affected by WB was appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 32 publications
6
45
1
1
Order By: Relevance
“…The affected areas show histological changes characterized by polyphasic myodegeneration and necrosis, infiltration of macrophages and heterophils, as well as interstitial connective-tissue accumulation ( Sihvo et al., 2014 ). Wooden breast disorder impairs the appearance and technological and nutritional properties of breast meat and negatively affects consumer purchases ( Soglia et al., 2015 ; Xing et al., 2020 ). Considerable studies have been conducted to investigate the possible etiologies leading to the development of WB myopathy, suggesting that localized hypoxia, oxidative stress, inflammatory responses, fiber-type switching, and metabolic shift are multifactorial components of this myopathy ( Petracci et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The affected areas show histological changes characterized by polyphasic myodegeneration and necrosis, infiltration of macrophages and heterophils, as well as interstitial connective-tissue accumulation ( Sihvo et al., 2014 ). Wooden breast disorder impairs the appearance and technological and nutritional properties of breast meat and negatively affects consumer purchases ( Soglia et al., 2015 ; Xing et al., 2020 ). Considerable studies have been conducted to investigate the possible etiologies leading to the development of WB myopathy, suggesting that localized hypoxia, oxidative stress, inflammatory responses, fiber-type switching, and metabolic shift are multifactorial components of this myopathy ( Petracci et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This myopathy has been garnering tremendous attention as the affected fillets have unappealing appearance and impaired functional properties during processing 3 . Moreover, the occurrence of WB myopathy has been reported on a global scale, and the incidence has increased dramatically over the past few years, 4,5 which causes substantial economic losses to the modern poultry industry.…”
Section: Introductionmentioning
confidence: 99%
“…A C-LM3B tenderization analyzer (Northeast Agricultural University, Harbin, China) was used to conduct shear force tests according the method of Xing [ 18 ]. Cubes were packaged in plastic bags individually and then heated in 80 °C water bath until the core temperature reached 75 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of meat quality found that shear force and compression force in WB are significantly higher than those in the normal breast (NB) [ 14 , 17 ], thus causing low consumer acceptance and economic loss. Xing [ 18 ] surveyed the incidence of WB in China, and the proportion was approximately 61.9%. Kuttappan [ 16 ] estimated that WB caused approximately $200 million economic losses due to trimming, drip loss, cook loss, downgrading and discarding.…”
Section: Introductionmentioning
confidence: 99%